The health and educational impact of removing financial constraints for school sport. (February 2023) - Sulz, Lauren Denise; Gleddie, Doug Lee; Kinsella, Cassidy; Humbert, M. Louise
Financial barriers often restrict sport participation among children from low-income families. Schools are thought to offer equitable access to programming, including school sport participation. However, pay-to-play school sport models can inhibit participation among students from low-income households. Recognizing the potential benefits of school sport and realizing the financial barriers to participation, the purpose of this study was to understand the extent to which school sport promotes educational experiences and holistic well-being of Canadian youth from low-income families. A case study was conducted with stakeholders who were supported by funding from a non-profit organization to help cover the costs of school sport registration fees. Data were collected from in-depth interviews with low-income students and their parents, teacher-coaches and school administrators. Three overarching themes were representative of the experiences of school sport participation among low-income students: (1) healthy student-athletes, (2) developing student-athletes in school, for life, and (3) supporting student-athletes as a community. The participants perceived that school sport participation offered holistic health benefits, and developed skills and behaviours that support positive educational experiences and foster life skills. Further, our results highlighted the importance of the school community in supporting low-income students to participate in school sport teams and the need to reframe school sport to better support low-income families.